(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
Ecological and agricultural risks of heavy metal pollution of soils in risky areas around Kapan City (RA) were investigated. Soil samples were collected in June 2013 and analyzed for Cr, Mn, Ni, Cu, Zn, As, Mo, Cd, Pb, Co, Hg by the mass spectrometric method. The investigations showed that the soils around Kapan copper-molybdenum combine and Geghanush tailing dump were significantly polluted with heavy metals, which may have posed serious risks not only to soil biological health, but also to agricultural production.